Profiling Wildlife Crimes Prosecuted Federally by the United States - Sosnowski, Monique C.; Kim, Yuna; Petrossian, Gohar A.; Asner, Marcus (Frontiers in Conservation Science, 2022)
Wildlife crime threatens national and global security. Much of the impact of wildlife crime is felt overseas, often in developing countries, where it threatens to catalyze conflicts, hinders economic development, undermines the rule of law, and threatens peace, amongst having other negative socio-economic and security impacts. But the impact of wildlife crime also is felt in United States, both directly by undercutting state and local conservation efforts, and indirectly, by injecting illegal wildlife and wildlife products into United States markets. While some work has delved into the sentencing dynamics of broader environmental crime in the United States, little research has explored the sentencing of wildlife crime, which is recognized as being distinct in nature by both governmental bodies and academics alike. The current study explores the federal prosecutions of wildlife crimes, focusing on profiling the wildlife crime cases charged by the US Department of Justice (DOJ). By profiling cases, we aim to explore (1) the application of charges associated with wildlife crime cases via their judgment documents; (2) the wildlife species involved in prosecuted cases; (3) the distribution of cases across US federal districts; and (4) and the sentencing patterns of wildlife crimes. Further statistical analyses explore the relationships between a variety of the variables extracted. Policy recommendations are set forth accordingly.